Illuminating the Deep: The Biology, Ecology, and Bioluminescent Adaptations of the Sharpear Enope Squid (Ancistrocheirus lesueurii) - Ma, Qinghe (International Journal of Natural Resources and Environmental Studies, 2026)
The Sharpear Enope squid (Ancistrocheirus lesueurii) is a highly adapted mesopelagic cephalopod found across the world’s tropical and subtropical oceans. Living in the deep-sea twilight zone, it is uniquely characterized by photophores, light-producing organs on its mantle, head, and arms, used primarily for counter-illumination, a camouflage technique that masks its silhouette from predators below. Additionally, A. lesueurii possesses sharp, chitinous hooks on its tentacular clubs instead of traditional suckers, enhancing its efficiency in capturing mesopelagic fishes and crustaceans. This article synthesizes research on the squid’s anatomical specializations, diel vertical migration, and ecological role as both a mid-water predator and vital prey for apex predators like sperm whales, offering insights into deep-sea food web dynamics.